A formação do pedagogo e o ensino da matemática nos anos iniciais do ensino fundamental - Lima, Simone Marques (2011)
The present dissertation is the result of a master‟s research in Education, developed through the Postgraduate Program in Education of Federal University of Mato Grosso (UFMT). Starting from the research theme “The teacher training and the teaching of Mathematics” the proposal is to discuss the formation of that professional, and also the challenges and problems faced by him/her when it comes to teaching Mathematics to the 1st and 2nd grades of Elementary School. The problem presented from the investigation object is: What are the challenges faced by the professional graduated in Pedagogy when teaching Mathematics to the initial grades of the Elementary School. The main objective of the following dissertation is to understand and identify how those professionals mobilize appropriate mathematical knowledge in the Pedagogy course. It seeks to understand which Math teaching conception serves as basis for the teacher pedagogical practice and what he/she thinks about his/her formation; it seeks the difficulties and challenges which that teacher faces to teach Mathematics. The chosen investigation scenario is the municipal public education system of Rondonopolis-MT. Eight teachers responsible for teaching Mathematics to the mentioned grades were invited to collaborate with the study. The curriculum and menus of disciplines related to the Math formation of the teacher of five Pedagogy courses of Mato Grosso were analyzed. Interpretative qualitative approaches were used as methodology framework, and also data collection, questionnaire, semistructured interview and documents analysis. As an aid to the reflection about the organization of the Pedagogy course we have Bissoli da Silva (2006), Libâneo (1998), Pimenta (1996), Franco (2008), Sheibe (2009), Gatti e Nunes (2008). When it comes to Math teaching we have as an aid to our discussions Skovmose (2001), Fiorentini (1995), Piaget (1990, 1988), Curi (2004). Finally, referring to teachers formation: Freire (1987, 1999), Veiga (2009), Kincheloe (1997), Contreras (2002), Peter Mclaren (1997), Giroux (1997), Gadotti (1995), Saviani (1991), Carvalho (2005), Nóvoa (1992, 2009), Paro (2008), Pinto (2000), Tardif (2002) e Shulman (1986, 1987 apud Montalvão e Mizukami 2002). The results of the research revealed the Mathematics teachers of the 1st and 2nd grades of Elementary School in this municipal public education system are not educators, even though the study seeks for educators. It also showed some gaps in the programs of initial formation of educators, especially in Mathematics. The teachers‟ conception about the teaching-learning process of Mathematics is, in the majority, according to the perspective of construction which gives more value to the process than to the product of math knowledge production. The faced challenges when teaching math to the first grades of Elementary School are related to the teacher formation and to the organization of school, and it essentially has a pedagogic nature: the insufficient appropriation of math contents to be taught, evaluation and teaching strategy to be chosen for teaching heterogeneous classes due to learning levels, and the problem of students learning deficit.